Engaging HIV-HCV co-infected patients in HCV treatment: the roles played by the prescribing physician and patients' beliefs (ANRS CO13 HEPAVIH cohort, France) - Salmon-Ceron Dominique; Cohen Julien; Winnock Maria; Roux Perrine; Sadr Firouze; Rosenthal Eric; Martin Isabelle; Loko Marc-Arthur; Mora Marion; Sogni Philippe; Spire Bruno; Dabis François; et al. (BMC, 2012)
Abstract Background Treatment for the hepatitis C virus (HCV) may be delayed significantly in HIV/HCV co-infected patients. Our study aims at identifying the correlates of access to HCV treatment in this population. Methods We used 3-year follow-up data from the HEPAVIH ANRS-CO13 nationwide French cohort which enrolled patients living with HIV and HCV. We included pegylated interferon and ribavirin-naive patients (N = 600) at enrolment. Clinical/biological data were retrieved from medical records. Self-administered questionnaires were used for both physicians and their patients to collect data about experience and behaviors, respectively. Results Median [IQR] follow-up was 12[12-24] months and 124 patients (20.7%) had started HCV treatment. After multiple adjustment including patients' negative beliefs about HCV treatment, those followed up by a general practitioner working in a hospital setting were more likely to receive HCV treatment (OR[95%CI]: 1.71 [1.06-2.75]). Patients followed by general practitioners also reported significantly higher levels of alcohol use, severe depressive symptoms and poor social conditions than those followed up by other physicians. Conclusions Hospital-general practitioner networks can play a crucial role in engaging patients who are the most vulnerable and in reducing existing inequities in access to HCV care. Further operational research is needed to assess to what extent these models can be implemented in other settings and for patients who bear the burden of multiple co-morbidities.